Climate resilient production practices: Extent of adoption and barriers faced by rice farmers in Telangana state of India - Waris, Amtul; Kumar, Rapolu Mahender; Kuchi, Surekha; Nirmala, Bandumula; Swarnaraj, Arun Kumar; Meera, Shaik Nagoor (Journal of Cereal Research, 2019)
Improving farm level adoption of climate resilient rice production practices is essential to enable farm families to improve their household food security. The present study was undertaken to analyze the farmers’ awareness, adoption and barriers to adoption of selected climate resilient rice production practices. Primary data were collected from 120 farmers from six villages based on random sampling in Nalgonda district of Telangana State, India. Visual questionnaire (photo elicitation) was used to assess farmers’ awareness and adoption of selected climate-resilient practices viz., System of Rice Intensification (SRI), Direct Seeded Rice (DSR), Green Manuring, Integrated Nutrient Management (INM), Leaf Color Chart (LCC), drought tolerant rice varieties and crop diversification. The findings of the study indicated that 50 percent of the farmers were aware of SRI practice but none of them were adopting it, similarly, 20 per cent of the farmers were aware of integrated nutrient management but only less than two percent had adopted the practice. A very low percentage of farmers were aware of the use of LCC (13.5%), drought tolerant paddy varieties (8.2%) with equally low adoption of these practices. Shortage of labor to adopt SRI, non-availability of drum seeder, small farm size, non-availability of seeds of green manure crops, formation of soil cracks in SRI, non-availability of LCC and drought resistant paddy varieties were the foremost barriers reported by farmers. The physical barriers reported by farmers need to be addressed to enhance adoption of climate resilient rice production practices. Similarly, training programs are to be organized to enhance the adoption of knowledge and skill intensive practices like SRI, DSR and LCC to overcome the non-physical barriers for adoption of climate resilient rice production practices.DOI:https://doi.org/10.25174/2249-4065/2019/94868